The Sea Ice Drift Forecast Experiment (SIDFEx): Introduction and Applications ... - Ludwig, Valentin; Goessling, Helge; SIDFEx Team (Zenodo, 2023)
The poster was presented at the European Geophysical Union (EGU) General Assembly 2023. It introduces the Sea Ice Drift Forecast Experiment (SIDFEx) database. SIDFEx comprises more than 180k lagrangian forecasts for the tracks of single assets (mostly buoys) in the Arctic and Antarctic. Applications are, amongst others: Pre-cruise planning Operational support during cruises for track planning and ordering of SAR images Consensus forecasts combining short- and long-term forecasts A webtool for interactive analysis Forecasts of sea-ice deformation. ... : The SIDFExplore project is funded by the German Federal Ministry of Education and Research (Bundesministerium für Bildung und Forschung/BMBF) under the grant number 03F0868A. ...